Hippocampal synaptoproteomic changes of susceptibility and resilience of male rats to chronic social isolation - Peric, Ivana; Costina, Victor; Gass, Peter; Findeisen, Peter; Filipović, Dragana (Brain research bulletin, 2021)
The susceptibility of an individual to chronic social isolation (CSIS) stress may cause major depression (MD) whereby some individuals are resistant to the stress. Recent studies relate MD with altered expression of synaptic proteins in specific brain regions. To explore the neurobiological underpinnings and identify candidate biomarkers of susceptibility or resilience to CSIS, a comparative proteomic approach was used to map hippocampal synaptic protein alterations of rats exposed to 6 weeks of CSIS, an animal model of depression. This model generates two stress-response phenotypes: CSIS-sensitive (depressive-like behaviour) and CSIS-resilience assessed by means of sucrose preference and forced swim tests. Our aim was to characterize the synaptoproteome changes representative of potential long-term changes in protein expression underlying susceptibility or resilience to stress. Proteomic data showed increased expression of glycolytic enzymes, the energy-related mitochondrial proteins, actin cytoskeleton, signalling transduction and synaptic transmission proteins in CSIS-sensitive rats. Protein levels of glutamate-related enzymes such as glutamate dehydrogenase and glutamine synthetase were also increased. CSIS-resilient rats showed similar proteome changes, however with a weaker increase compared to CSIS-sensitive rats. The main difference was observed in the level of protein expression of vesicle-mediated transport proteins. Nonetheless, only few proteins were uniquely up-regulated in the CSIS-resilient rats, whereby Cytochrome b-c1 complex subunit 2, mitochondrial (Uqcrc2) and Voltage-dependent anion-selective channel protein 1 (Vdac1) were uniquely down-regulated. Identified altered activated pathways and potential protein biomarkers may help us better understand the molecular mechanisms underlying synaptic neurotransmission in MD or resilience, crucial for development of new therapeutics.